Relationship between teachers' motivation and the quality of teaching in primary schools in Makkah, Saudi Arabia - Jusoh, Rosnani; Mlibari, Nada Abdul Raheem M. (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The aim of this study is to examine the relationship between motivation and quality of teaching by examining the set of factors that influence Makkah primary school teachers. Based on Keller’s and Abraham Maslow’s theories of motivation, a model is developed and tested to examine teachers’ motivational factors to quality teaching. Five precursors (interest, relevance, expectation, satisfaction and self-actualisations) of quality teaching are presented in the model. The analysis procedure made use of descriptive statistics and bivariate correlation. The findings reveal that there is a reasonably high quality teaching among Makkah primary school teachers. In addition, the result indicated a significant positive relationship between the independent variables (interest, relevance and self-actualisation) and the dependent variable (quality of teaching).